Pengaruh PAD, DAU dan DAK pada Alokasi Belanja Modal dengan Pendapatan Per Kapita Sebagai Pemoderasi - Sari, Desak Made Mya Yudia; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p16, 2018)
Capital e xpenditure s are budget expenditur s e for acquisition of property, plant and other assets that provide benefits over one accounting period. Capital expenditure has an important influence on the economic growth of a region and helps moving the regional economy. Factors affecting capital expenditures include local revenues, general allocation funds and special allocation funds. The purpose of this study is to determine the effect of local revenues, general allocation funds, and special allocation funds in the allocation of capital expenditures in the regencies / cities in Bali and to determine whether the influence of local revenue, general allocation funds and special allocation funds on the allocation of capital expenditure is moderated by per capita income. The sample of this research is government of Regency / City in Bali during the period of 2012-2016 , resulting in of 45 observation. Data analysis techniques used are multiple linier regression analysis and m oderated r egression a nalysis. Based on the results of the analysis it is known that the local revenue and special allocation funds have positive effect s on the allocation of capital expenditure while the general allocation fund does not affect the allocation of capital expenditure. Per capita income do es not moderate the effects of local revenue, general allocation funds and special allocation funds on capital expenditure allocations. Keyword: Original local government, general allocation funds, special allocation fund, per capita income, andcapital expenditure